Anticipating PTSD in severe COVID survivors: the case for screen-and-treat. Issue 1 (31st December 2022) - Greene, Talya; El-Leithy, Sharif; Billings, Jo; Albert, Idit; Birch, Jennifer; Campbell, Mari; Ehntholt, Kim; Fortune, Lorna; Gilbert, Nicola; Grey, Nick; Hana, Laurinne; Kennerley, Helen; et al.
ABSTRACT: Based on research from previous pandemics, studies of critical care survivors, and emerging COVID-19 data, we estimate that up to 30% of survivors of severe COVID will develop PTSD. PTSD is frequently undetected across primary and secondary care settings and the psychological needs of survivors may be overshadowed by a focus on physical recovery. Delayed PTSD diagnosis is associated with poor outcomes. There is a clear case for survivors of severe COVID to be systematically screened for PTSD, and those that develop PTSD should receive timely access to evidence-based treatment for PTSD and other mental health problems by multidisciplinary teams. HIGHLIGHTS: We anticipate that up to 30% of survivors of severe COVID will develop PTSD, yet PTSD is frequently undetected in primary and secondary care settings. There is, therefore, a clear case for establishing systematic screening and ensuring timely access to treatment.